Evolving Challenges in the Implementation of China’s “Four Frees and One Care” Policy for HIV/AIDS - Xie Z; Duan Z (Dove Medical Press, 2024)
Ziyi Xie,1 Zhizhuang Duan2 1Faculty of Humanities and Social Science, Macao Polytechnic University, Macao, People's Republic of China; 2Xingzhi College, Zhejiang Normal University, Jinhua, People's Republic of ChinaCorrespondence: Zhizhuang Duan, Xingzhi College, Zhejiang Normal University, Postal Address No. 3388 Yingbin Avenue, Jinhua, Zhejiang Province, People's Republic of China, Email 105009342@qq.comAbstract: In response to the HIV/AIDS epidemic, China initiated the "Four Frees and One Care" policy in late 2003. This policy provided free counseling, testing, and antiretroviral treatment for people living with HIV, while also offering support to affected families. While instrumental in advancing HIV/AIDS prevention, the policy faces evolving challenges. This study aims to analyze this challenge from multiple dimensions and, based on this analysis, provide effective recommendations for the Chinese government to address it, promoting the sustainable development of the "Four Frees and One Care" policy. The research found that reduced government funding has led to the decline of grassroots organizations, creating a disconnect between administrative and treatment systems. Additionally, advancements in medical technology introduce new antiretroviral drugs, complicating their integration into the healthcare system. In the current healthcare reform, updating the list of free antiretroviral drugs proves challenging. Adapting the policy to contemporary HIV/AIDS prevention should be a priority for the Chinese government. Balancing financial constraints, organizational sustainability, and evolving medical technologies will be pivotal for the ongoing transformation of the "Four Frees and One Care" initiative.Keywords: Four Frees and One Care, ART, PLHIV, China, HIV/AIDS policy